Digital Content Stimuli and Visit Intention toward a Korean-Themed Café: The Mediating Role of Muslimah Emotional Connection - Ulfah Nurwahidah; Bethani Suryawardani; Ganjar Mohamad Disastra (Yayasan Sinergi Kawula Muda, 2026)
This study investigates how User Generated Content (UGC) and Firm Generated Content (FGC) are associated with Visit Intention (VI), with Muslimah Emotional Connection (MEC) as a mediating variable in the context of Korean-themed café as a creative space. Although previous studies have widely examined the relationship between digital content and visit intention, limited research has explored how identity and emotional connections influence Muslimah consumers within Hallyu-inspired spaces. This study addresses this gap by conceptualizing MEC as an emotional mediator that reflects emotional comfort, identity congruence, and alignment with personal and religious values in the context of Korean-themed café experiences. Kolato Café in Bandung was selected as the research context due to its strong Hallyu-themed branding and active Instagram presence. Using the Stimulus-Organism-Response (SOR) framework and the Theory of Interpersonal Behavior (TIB), this study employed a quantitative approach involving 292 respondents and analyzed the data using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that both UGC and FGC significantly influence MEC and VI, with UGC demonstrating a stronger influence on emotional connection (β = 0.481) compared to FGC. In addition, MEC partially mediates the relationships between digital content and visit intention. These findings extend the application of SOR and TIB by showing that emotional engagement among Muslimah consumers is shaped not only by digital attractiveness, but also by authenticity, emotional reassurance, and value compatibility. Practically, the study suggests that Korean-themed café businesses should encourage authentic consumer participation and develop culturally sensitive digital marketing strategies that strengthen emotional connection among Muslimah audiences.